Correlation between diaphragmatic mobility by transthoracic ultrasound and echocardiography findings in patients with idiopathic pulmonary fibrosis - Adel M Saeed; Ibraheem Dwidar; Eman B AbdelFattah; Khaled Y Elnady; Mustafa R Nagdy (Egyptian Journal of Chest Disease and Tuberculosis, 2022)
Background Idiopathic pulmonary fibrosis (IPF) is known as a particular pattern of persistent gradually developing fibrosing interstitial pneumonia of unspecified cause that takes place mainly in elder adults, is restricted to the lungs, and is correlated with the radiological and/or histopathological pattern of usual interstitial pneumonia. Patients with IPF exhibit characteristic features regarding the respiratory and cardiac muscle function. The lack of an association between diaphragmatic mobility and echocardiography findings of right and left ventricle functions in patients with IPF was unexpected as transthoracic ultrasound (US) and echocardiography are feasible, reproducible, noninvasive, and largely adopted in the clinical practice and in clinical trials. Objective To correlate between diaphragmatic mobility using transthoracic US and ventricular functions using echocardiography in patients with IPF. Patients and methods A prospective case–control study was conducted in which 40 patients with IPF and 10 controls underwent transthoracic US assessment of diaphragmatic excursion and echocardiography study, and then the results were correlated. Results There was a statistically significant decrease in deep breathing excursion, right ventricle functional area change, tricuspid annular plane systolic excursion, and ejection fraction in addition to an increase in pulmonary artery systolic pressure among the study group. Both normal breathing excursion and deep breathing excursion have a positive correlation with right ventricle functional area change and tricuspid annular plane systolic excursion, whereas a negative correlation was seen with age and pulmonary artery systolic pressure in both study and control groups. Conclusions Transthoracic US assessment of diaphragmatic mobility can clearly reflect the right ventricle function in patients with IPF.